Health & Productivity Management Associated With Improved Efficiency of Inpatient Health Care: Cross-sectional Study Using FY2021 Bed Function Report - Hajime Watanabe MPH; Satoshi Miyata PhD; Satoru Kanamori RN, PHN, PhD; Yoshinori Nakata MD, MBA (SAGE Publishing, 2024)
This study examined the relationship between health and productivity management (H&PM) and inpatient health care efficiency in hospitals. This cross-sectional study is based on 1108 hospitals using data from the FY2021 Bed Function Report. The presence of Certified H&PM Organization was the proxy variable for H&PM implementation. The efficiency value obtained using the input-oriented Banker-Charners-Cooper model of data envelopment analysis was a proxy variable for inpatient health care efficiency. The input variables were the number of hospital beds, registered physicians, ward nurses, and other staff members in the ward. The output variable was the total number of patients in the ward per year. We conducted a Wilcoxon rank-sum test and compared certified and non-certified hospitals. The efficiency value was the objective variable, and certification presence was the explanatory variable. We used a stepwise method, including adjustment variables, to confirm whether the certification presence remained in the final multiple regression model. Efficiency was significantly higher in certified hospitals than non-certified hospitals. Certification presence remained in the final multiple regression model (β = .027, CI = −0.004 to 0.057, P = .085). Although not statistically significant, certified hospitals tended to have higher efficiency compared to non-certified hospitals. These findings suggested that hospitals that actively engage in H&PM may have higher efficiency in inpatient health care. However, further research is needed to establish the causal relationship.